2017
DOI: 10.1039/c7fo00991g
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective action of tea polyphenols on oxidative stress-induced apoptosis through the activation of the TrkB/CREB/BDNF pathway and Keap1/Nrf2 signaling pathway in SH-SY5Y cells and mice brain

Abstract: Many studies have shown that oxidative stress is a major cause of cellular injuries in a variety of human diseases including cognitive impairment. Tea polyphenols (TPs), natural plant flavonoids found in tea plant leaves, possess the bioactivity to affect the pathogenesis of several chronic diseases via antioxidant associated mechanisms. However, the possible antioxidant and neuroprotective properties of TPs in the brain of mice housed in constant darkness and in HO-stimulated SH-SY5Y cells are yet to be eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 51 publications
5
53
0
Order By: Relevance
“…For example, tea polyphenols can suppress the ROS release and reduction of SOD activities and apoptosis induced by glutamate in primary cortical neurons (Cong et al, 2016). Furthermore, tea polyphenols also possess neuroprotective activities via the activation of the Keap1/Nrf2 pathway in vitro and in vivo (Qi et al, 2017b). In this study, we found that tea polyphenols have protective effects against METH-induced toxicity.…”
Section: Discussionsupporting
confidence: 51%
“…For example, tea polyphenols can suppress the ROS release and reduction of SOD activities and apoptosis induced by glutamate in primary cortical neurons (Cong et al, 2016). Furthermore, tea polyphenols also possess neuroprotective activities via the activation of the Keap1/Nrf2 pathway in vitro and in vivo (Qi et al, 2017b). In this study, we found that tea polyphenols have protective effects against METH-induced toxicity.…”
Section: Discussionsupporting
confidence: 51%
“…GTPs possess higher antioxidant activity than vitamin E and vitamin C [26,27]. Our team and other researchers have reported that GTPs can improve CIRI outcomes in local cerebral ischemia-reperfusion and CPR models, relating to its effects of increasing SOD activity and decreasing ROS, MDA production [9,28]. At present, this study further confirmed that GTPs can produce endogenous antioxidant effects by promoting the expression of SOD1 (CuZn-SOD, mainly located in the BioMed Research International cytoplasm) and SOD2 (Mn-SOD, mainly located in mitochondria) in the brain.…”
Section: Discussionmentioning
confidence: 82%
“…Cerebral ischemiareperfusion injury (CIRI) is a very complicated cascade of reactions involving multiple mechanisms, such as oxidative stress, calcium overload, mitochondrial dysfunction, inflammatory reaction, and neuronal apoptosis [5][6][7]. Current researches have indicated that oxidative stress plays a vital role in the pathogenesis of CIRI with a characteristic of the imbalance of oxidative and antioxidant defense system [8,9]. When the redox balance is disturbed, accumulated free radicals trigger cell membrane lipid peroxidation and can also initiate neuronal apoptotic cascades through mitochondria, endoplasmic reticulum, or death receptors, resulting in neural dysfunction and cell death [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Study reported that the neuroprotective activity of tea polyphenols relied on the activation of the Keap1/Nrf2 signaling pathway. [27] To detect the effect of AC on Nrf2 translocation in MIN6 cells, in the present study ( Figure 6), the cells were treated with AC for 24 h and this signaling pathway was analyzed by Western blot using corresponding antibodies, the result showed that compared with untreated cells, treatment with AC significantly increased the nuclear Nrf2 in MIN6 cells ( Figure 6A), by 1.64 � 0.06 folds and 1.86 � 0.02 folds at the concentration of 0.8 mg/mL and 1.6 mg/mL, respectively ( Figure 6B), which indicated that AC could mediate the activation of antioxidant defense pathway Nrf2 in MIN6 cells.…”
Section: Effect Of Ac On Nrf2 Pathwaymentioning
confidence: 99%